Plastic pollution and marine conservation : approaches to protect biodiversity and marine life - Bonanno, Giuseppe; Orlando Bonaca, Martina (Academic Press, 2022)
"Plastic Pollution and Marine Conservation: Approaches to Protect Biodiversity and Marine Life provides comprehensive knowledge on the consequences of plastic waste in marine environments at different levels, ranging from ecological and biological, to social, economic and political. The book synthesizes historical information, gaps in current knowledge, and recent discoveries by illustrating the main stages that made plastics a global issue for ocean ecosystems and their wildlife. Written by international experts on marine pollution, marine biology, and management of environmental resources, this book explores the main topics of marine plastic pollution such as input quantification, polluting sources, ultimate fate, ecological consequences, and more. This an important resource for a wide audience, including marine conservationists, environmental managers, decision-makers, NGOs, private companies, and activists working to combat plastics in our seas and oceans. Illustrates the evolution of plastics, from revolutionary materials to global environmental emergency Discusses marine plastic pollution with scientific rigor and easy language that is supported by graphics and tables Led by a team of editors with expertise in biology, pollution, conservation and policies of marine wildlife, biodiversity and ecosystems."--